Evaluating the Impact of Corporate Social Responsibility (CSR) on Corporate Financial Performance: A Systematic Literature Review - Bahgyawan, Dylland Raihan (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2025)
This research examines the impact of Corporate Social Responsibility (CSR) on the financial performance of companies through a systematic review of 45 scientific articles published between 2018-2025. The study analyzes three main dimensions: the correlation of CSR with net profit, enhancement of company reputation, and comparison of CSR with financial indicators. The results indicate that CSR has a significant positive impact on the financial performance of companies, with company reputation acting as an important mediator in this relationship. The majority of studies show that companies that consistently implement CSR programs experience an increase in ROA, ROE, and long-term profitability. This research provides practical contributions for company management in integrating CSR strategies as a driver for sustainable financial performance.